Facile preparation of NiCo2O4 nanobelt/graphene composite for electrochemical capacitor application. (1st June 2015) - Xu, Jie; Li, Lei; Gao, Peng; Yu, Lei; Chen, Yujin; Yang, Ping; Gai, Shili; Yang, Piaoping
Graphical abstract: A hybrid composite containing one-dimensional NiCo2 O4 nanobelt and graphene nanosheets was prepared through a facile hydrothermal process followed by a suitable heat treatment, which shows improved rate capability and high cycle stability. Abstract: A hybrid composite containing ultrathin NiCo2 O4 nanobelts and graphene nanosheets was prepared through a simple and scalable hydrothermal method combined with suitable heat treatment. The optimal calcination condition has been optimized by investigating the pseudocapacitive behaviour of bare spinel NiCo2 O4 prepared at different calcination temperatures. It is found that the self-assembled microstructure of NiCo2 O4 nanobelts prepared at 250 °C (named as S250) exhibit superior electrochemical performance to those prepared at other temperatures. The composite comprising NiCo2 O4 nanobelts and graphene nanosheets (GS250) has enlarged specific surface area (222 m 2 /g), yielding a high specific capacitance of 1072.91 F/g at the current density of 1 A/g with desirable rate performance and cycling stability. In view of simple, high-yield synthetic route and remarkable electrochemical properties, this NiCo2 O4 nanobelt/graphene hybrid composite should be a promising electrode material for supercapacitors in high energy density storage systems.